Incendios forestales en el Estado de México en el periodo de diciembre de 1997 a junio de 1998 - Rivas Manzano, Irma Victoria; Fragoso Reyes, Nerea Josefina; García Medina, Jaime; Rivas González, Eric; Díaz Ascencio, Edith Patricia; Sánchez Colín, José Cruz (CIENCIA ergo-sum; Vol. 6 Núm. 3 (1999): CIENCIA ergo-sum (noviembre 1999-febrero 2000), 2017)
-